Bounding greed : worklife integration and positive coping strategies among faculty of color in early, middle, and late career stages at comprehensive universities - Guillaume, René O., 1980-; Martinez, Edna (Emerald Publishing Limited : Information Age Publishing, Inc., 2023)
Building on the work of Guillaume (2021), the collection of autoethnographies and testimonios in this book highlight positive coping mechanisms, strategies, and healthy boundaries that early, middle, and late-career Faculty of Color at comprehensive universities have deployed to negotiate home and work.As beautifully stated by Aeriel A. Ashlee, whose story you will find in chapter two: 'It is not a formula, a blueprint to copy, or a recipe to repeat;' however, we hope that the stories about relying on faith, family, mentors, culture, and community presented in the following chapters will support Faculty of Color in their own well-being and work-life integration efforts. Certainly, work-life balance or integration is not the solution to deeply entrenched systemic issues in higher education; however, research in the area of work-life balance/integration has affirmed the need for postsecondary institutions to place significant importance on the topic of work-life, in particular the need for increased support at both the department and institutional levels (Denson et al., 2018). Thus, it is also our hope that this book will serve as a resource for educational leaders in the area of faculty development, as well as academic administrators whose role is to recruit, retain, and evaluate Faculty of Color at comprehensive universities.
Keywords: Minority college teachers -- United States -- Attitudes.; Minority college teachers -- Job stress -- United States.; Minorities in higher education -- United States.; College teachers -- Workload -- United States.; Work-life balance -- United States.; Race discrimination -- Psychological aspects.; Education -- Schools -- Levels -- Higher.; Popular philosophy: Meaning of life, finding sense in life.; Higher education, tertiary education.; elektronické knihy; electronic books